Além de sol e cachoeiras: um olhar para o potencial educacional do patrimonio natural de Pirenópolis-GO/Brasil - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Considering that the municipality of Pirenópolis-GO, the spatial section of this work, has a unique Cerrado landscape, with several natural attractions, research was carried out on these natural areas, in their relationship with local schools. For this purpose, the urban and rural public schools of the municipality were listed, as well as the protected natural areas of the region as Conservation Units and the natural areas open to tourist visitation. The objective was to identify the educational potential existing in the local natural heritage, as well as to reflect on the practice of environmental education in local schools in relation to this heritage, with a view to proactive actions to appropriate this potential. On-site observation, interviews and semi-structured questionnaires for data collection and analysis were used as tools to support this research. Several criteria were raised to analyze the educational potential of natural areas from the perspective of the manager/owner, in which a qualitative and quantitative analysis of the responses was carried out, identifying the existing potential in each of the areas researched, as well as their educational index. The study revealed that the areas have preserved Cerrado, in addition to anthropic areas, with scenic beauty and infrastructure capable of receiving schools and, therefore, with educational potential, although two of them do not have infrastructure and are not yet open to visitors. The relationship between the schools surveyed and the natural areas is scarce and the few times they were accessed occurred at specific times, and there is no systematization for their knowledge. As a teaching strategy for Environmental Education, they use more videos and films and not classes in natural environments. Almost half of them have never visited a natural area with students. In the students' eyes, it was possible to perceive that, as a form of leisure, they know and access natural areas of the municipality that are more accessible to the community. The vast majority know these places through their family, and not through the school, and would like the school to hold classes in these environments. When analyzing the Political-Pedagogical Projects of the schools, it was found that, although they mention some projects and actions related to environmental issues, they do not highlight issues related to the local natural heritage. It is hoped that this work can contribute to schools and natural areas investing in environmental education activities and that they can plan actions in a collective and collaborative way, to overcome obstacles and make the city's natural heritage, as part of the Cerrado Goiano, known, valued and used as an educational space.
Beyond sun and waterfalls: a look at the educational potential of the natural heritage of Pirenópolis-GO/Brazil
Keywords: Áreas naturais - Cerrado; Educação ambiental - Cerrado; Cerrado - Meio ambiente - Potencial educacional e índice educacional; GEOGRAFIA::GEOGRAFIA REGIONAL; GEOGRAFIA FISICA::GEOECOLOGIA